2016
DOI: 10.1177/0956462415611514
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of intimate partner violence in HIV-positive women engaged in transactional sex in Mombasa, Kenya

Abstract: We evaluated the prevalence and correlates of intimate partner violence in the past year by a regular male partner in HIV-positive female sex workers in Mombasa, Kenya. This cross-sectional study included HIV-positive women ≥ 18 years old who reported engagement in transactional sex at the time of enrolment in the parent cohort. We asked 13 questions adapted from the World Health Organization survey on violence against women about physical, sexual, or emotional violence in the past year by the current or most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 59 publications
2
36
1
2
Order By: Relevance
“…Details of these methods are described elsewhere (28). New participants were recruited through community outreach activities at bars and hotels and informational meetings at our clinic.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of these methods are described elsewhere (28). New participants were recruited through community outreach activities at bars and hotels and informational meetings at our clinic.…”
Section: Methodsmentioning
confidence: 99%
“…Most FSWs in Africa also have long-term boyfriends or husbands (26, 27). Studies from Kenya that focused on IPV (variously defined) against FSWs have reported estimates ranging from 15% (28) to 70% (27). Individual, dyad, and community-based interventions that strengthen women's communication and coping skills have been shown to reduce IPV and negative health consequences in other settings (21, 29-31).…”
Section: Introductionmentioning
confidence: 99%
“…At enrollment and annual visits, women who reported a current or most recent regular male sex partner were asked if they had experienced intimate partner violence (IPV) by that partner ever and in the past 12 months. 17 Intimate partner violence was defined as report of 1 or more of 13 items corresponding to acts of psychological, physical, and sexual violence. 18 An additional set of questions assessed whether women had experienced physical or sexual violence from anyone other than a current or most recent regular sex partner since the age of 15.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the association between baseline IPV and (1) linkage to care and (2) initiation of ART at 4 months, we used logistic regression models adjusted for potential confounding variables, including age, literacy, income, mobile phone ownership, educational status, age at sexual debut, primary partnership status, number of clients, age at initiation of sex work, time since HIV diagnosis, study site, and randomization arm. 16 Covariates were selected based on being theoretical confounders of the relationship between IPV and HIV-care–related outcomes. 16 , 23 27 We first modeled any IPV (physical and/or sexual).…”
Section: Methodsmentioning
confidence: 99%
“… 13 , 14 FSW are at an elevated risk of IPV, both from commercial and noncommercial romantic partners, which may contribute to their increased risk of HIV acquisition as well as HIV-related outcomes. 15 , 16 A substantial proportion of FSW living with HIV are not currently engaged in care or virally suppressed. 17 19 The existing evidence of the effect of IPV on HIV care outcomes among FSW is mixed, with 1 study reporting lower risk of detectable viral load among FSW experiencing IPV, 15 and another reporting an association between violence from sexual partners and worse outcomes.…”
Section: Introductionmentioning
confidence: 99%